Moderate to severe chronic arteriolar lesions is an independent risk factor for adverse renal outcomes in IgA nephropathy. - Qian Wu; Yi Chen; Miaoying Shen; Yuyuan Cai; Haokai Yu; Lei Zhou; Haifeng Yang; Chuan Zou (PLoS ONE)
Background The impact of chronic arteriolar lesions on the prognosis of IgA nephropathy remains controversial. This study aims to explore the value of chronic arteriolar lesions of varying degrees in predicting the prognosis of IgA nephropathy patients and analyze the associated risk factors that contribute to the formation. Methods A retrospective analysis was conducted on 853 patients diagnosed with IgA nephropathy through renal biopsy at Guangdong Provincial Hospital of Traditional Chinese Medicine between September 1, 2005, and December 31, 2021. Eventually, a total of 574 cases were included in this study. According to the degree of chronic arteriolar lesions, the patients were divided into four groups: no lesion group (n=115), mild lesion group (n=287), moderate lesion group (n=131), and severe lesion group (n=41). Relevant clinical and pathological features and renal outcomes were recorded. Kaplan-Meier analysis, Cox proportional hazards regression, and receiver operating characteristic (ROC) curve analysis were utilized to examine the relationship between different degrees of chronic arteriolar lesions and the prognosis of IgA nephropathy. Additionally, risk factors associated with the development of moderate to severe chronic arteriolar lesions were identified. Results Worse clinical and pathological features were observed in the moderate to severe lesions group (P<0.05). Moderate to severe chronic arteriolar lesions (aHR=3.357, 95%CI: 1.018-11.071, P=0.047), creatinine, S1, E1, T2, and C2 were identified as independent risk factors for adverse renal outcomes. Cox multivariate regression analysis on moderate to severe chronic arteriolar lesions demonstrated that creatinine, T2, and C2 were independent risk factors for adverse renal outcomes in patients with moderate to severe chronic arteriolar lesions. Conclusion Moderate to severe chronic arteriolar lesions independently increases the risk of adverse renal outcomes.